ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PERSONEL MELALUI BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Pada Pangkalan TNI AU Supadio) - B31112156, WIDYA GUSMAN (Jurnal Manajemen Update, 2015)
Personnel performance is a benchmark in determining whether or not the performance of theorganization. Transformational leadership is a leadership style that is appropriate in shaping theorganizational culture in order to improve the performance of personnel in the Supadio Air Force Base.This study aims to analyze the influence of transformational leadership on the performance ofpersonnel through organizational culture as an intervening medium in Supadio Air Force Base. Tofacilitate troubleshooting, research was conducted by using linear regression analysis, path analysis,and Cronbach alpha using SPSS 15.0. The variables used in this research is independent ofTransformational Leadership, Organizational Culture as an intervening medium and personnelperformance as the dependent variable. This research uses the questionnaire data from a sample of 70respondents. In accordance with the above research goal, so in this research was formulated by 3hypotheses. The first hypothesis,  transformational leadership has significant positive effect onorganizational culture. The second hypothesis, Organizational Culture has significant positive effect onpersonnel performance. The third hypothesis, transformational leadership has significant positive effecton personnel performance .The results of this research indicate that, Transformational Leadership hassignificant positive effect on organizational culture. Organizational culture has significant positive  effect in mediating the effect of transformational leadership on personnel performance. Where asTransformational Leadership is not  significant positive impact on the personnel performance atSupadio Air Force Base. Suggestions for further research, when using the questionnaire data should bedone with direct interviews in order to avoid  respondents' answers from misunderstanding grainsquestions in the questionnaire. It also needs to be added variables are still closely related to thevariables used in this research.  Keywords: Transformational Leadership, Organizational Culture, and Personnel Performance .